The Functioning’s Features of the Reflective Competence as a Complete System - Savchenko, Olena (Psychological Prospects Journal, 2016)
The author analyzes the reflective competence as an integrative personal formation, which appeared in the process of the reflective experience to ensure the high productivity of the reflectivity’s realization by means of converting potential forms into actual results and achievements. The competence in the experience’s structure provides the performance of two functions: the activation of the subject’s activity in the nomination and achievement of new goals, the maintaining of the integrity as an important condition for the functioning and development of the system. The conducting of the empirical data’s secondary factorization allowed to determine the system’s generalized properties of the reflective competence that characterized the dynamic aspects of its existence. There were identified three groups of factors. The first factors’ group integrates the functions that provide an effective solution of the reflective tasks arising during the different forms of the object-practical activities, and development of reflective competence as a complete integrative formation (the incentive functions). Among the incentive functions of the reflective competence we have identified some: the formation of the activity’s program, the expansion of the information provision, the modeling of the future and the definition of the developmental prospects, the prediction of own life’s events. Тhe subject’s intention to make a quick decision in uncertain situations, resulting in impulsive style, is a factor that controls the system development and hinders its effective functioning. The symptom complexes, formed in the reflective experience, unite some varied elements. These symptom complexes provide the stability of the reflective competence as an integrative system. The important factor of the system’s effective functioning is the combining of the following elements such as: the system of the evaluative criteria of the reflective activity and the skills to introspect self-analysis, the rational strategies of a problem solving and the skills to control mental activities, the productive means of a problem solving and the features of the self-evaluation, the personal aspirations and the expectations of positive results, the skills to organize a problem solving process and the motivation to raise own conversance on the theme “Reflection”. Keywords: reflectivity, competence, reflective competence, reflective experience, a systematic approach.